SUPLEMENTASI KREATIN DAN PERFORMA KOGNITIF PADA KONDISI DEPRIVASI TIDUR: TINJAUAN SISTEMATIS - Muhammad Abdul Lathif Kariim (Bajang Institute, 2025)
Background:Sleep deprivation is an increasingly common condition in modern society, particularly among populations with high work demands such as healthcare workers and shift workers. This condition is known to adversely affect cognitive function, especially attention, working memory, and processing speed. Creatine, which plays a role in brain bioenergetics through the creatine–phosphocreatine system, has been proposed as a nutritional intervention to help maintain cognitive function during metabolic stress conditions such as sleep deprivation. Objective: This systematic review aimed to evaluate the effects of creatine supplementation on cognitive performance in healthy adults experiencing sleep deprivation. Methods:A systematic literature search was conducted in PubMed, ScienceDirect, and Google Scholar in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Included studies were randomized controlled trials that investigated creatine supplementation under conditions of sleep deprivation and reported cognitive outcomes. Data were extracted and synthesized narratively due to the limited number of studies and heterogeneity in study designs. Results:Three randomized controlled trials met the inclusion criteria. Overall, creatine supplementation demonstrated a protective effect against sleep deprivation–induced cognitive decline, particularly in energy-sensitive cognitive domains such as reaction time, attention, working memory, and processing speed. However, not all cognitive outcomes showed statistically significant differences, indicating that the effects of creatine are selective. Additional evidence suggested that improvements in cognitive performance were associated with increased levels of high-energy phosphate compounds in the brain. Conclusion: Creatine supplementation shows potential as a supportive nutritional strategy to preserve cognitive function during sleep deprivation, although the available evidence remains limited and heterogeneous. Further well-designed studies with larger sample sizes, standardized protocols, and real-world populations are needed to strengthen the clinical implications of these findings.